Food insecurity and disability in the United States. Issue 2 (April 2019) - Heflin, Colleen M.; Altman, Claire E.; Rodriguez, Laura L.
Abstract: Background: Households with a disabled adult are disproportionately food insecure, yet the mechanisms linking food insecurity to disability are under-specified. Objective: To develop and empirically examine a model of the potential pathways connecting specific types of disability with food insecurity. Methods: With pooled, repeated cross-sectional National Health and Nutrition Examination Survey data (1999–2014) including 38, 354 participants, we ran probit models to estimate the probability of being food insecure as a function of different sets of disability measures and our control variables. We explored the extent to which these patterns differed for prime-aged individuals (19–59) from those age 60 and older. Results: Work-limiting disabilities, functional limitations, and trouble managing money were associated with an increased likelihood of food insecurity for both prime-aged and older individuals, net of other forms of disability. Mobility limitations, trouble seeing, and trouble hearing increased the likelihood of food insecurity for prime-aged individuals only. Conclusion: These findings suggest that disabilities are associated with food insecurity through multiple pathways. Revised public health and policy solutions are needed to address the high rates of food insecurity among those with disabilities.